Proudly we can be Africans : Black Americans and Africa, 1935-1961 - Meriwether, James Hunter, 1963- (University of North Carolina Press, 2002)
In the mid-20th century nations across Africa fought for their independence from colonial forces. By examining black Americans' attitudes toward and responses to these struggles, this work probes the shifting meaning of Africa in the intellectual, political and social lives of African Americans.
Keywords: African Americans -- Relations with Africans.; African Americans -- Race identity.; African Americans -- Intellectual life -- 20th century.; United States -- Relations -- Africa.; Africa -- Relations -- United States.; Africa -- Politics and government -- 20th century.; Africa -- Social conditions -- 20th century.; Black people -- Civil rights -- Africa -- History -- 20th century.; Civil rights movements -- Africa -- History -- 20th century.; Noirs américains -- Relations avec les Africains.; Noirs américains -- Identité ethnique.; Noirs américains -- Vie intellectuelle -- 20e siècle.; Afrique -- Relations -- États-Unis.; Afrique -- Politique et gouvernement -- 20e siècle.; Afrique -- Conditions sociales -- 20e siècle.; Mouvements des droits de l'homme -- Afrique -- Histoire -- 20e siècle.; Personnes noires -- Droits -- Afrique -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; Black people -- Civil rights; African Americans -- Intellectual life; African Americans -- Race identity; African Americans -- Relations with Africans; Civil rights movements; International relations; Politics and government; Social conditions; Africa; United States; 1900-1999; History